KUALITAS DAN KEPUASAN MASYARAKAT TEHADAP PELAYANAN ADMINISTRASI BPJS KANTOR CABANG TUBAN - jurnalmap map; Yusdhitira Christiono; Hadi Susanto; Arini Sulistyowati (MAP (Jurnal Manajemen dan Administrasi Publik), 2021)
One of the goals of health services is to increase the degree of community life, because with good health will be able to make the community independent and can create prosperity for themselves. Health is a basic human need to live properly and carry out its role in society, so as to obtain prosperity. This study aim to determine and describe the quality of BPJS Health membership service in Tuban Operational Office. The method used is Service Quality (SERVQUAL). The sampling technique is using accidental sampling technique. The result showed that the quality of BPJS Health service in Tuban Operational Office was still not in line with community expectation, because the Q value was calculated base on the service quality formula Ôëñ 1. The value of each dimension was as follows : Tangible dimension 0.928; Reliability dimension 0.923; Responsiveness dimension 0.721; Assurance dimension 0.704; and Empathy dimension 0.872. With an average value of service quality of 0.8296.Keywords : service quality, servqual, BPJS health